(untitled) (The Chittagong University Journal of Science, 2021)
A series of diastereoisomeric square planar nickel(II) diperchlorate complexes, [Ni(L)](ClO4)2L= isomeric Me8[14]ane (LAα, LBα or LCα)undergo axial ligand addition reactions with NO3-, Cl-, Br-, SCN- or ClO4- to yield six coordinate octahedral derivatives [NiL(X)x(Y)y].z(H2O)(X=NO3,Cl, Br or SCN; Y= ClO4; x = 1 or 2; y = 1 or 0 and z = 0, 1 or 2). The products have been characterized on the basis of analytical, spectroscopic, magnetic and conductance data. All the derivatives are unstable in open air except one derivative and revert back to original square planar complexes. Antifungal activities of the ligands and their nickel(II) complexes have been investigated against some phytopathogenic fungi. The Chittagong Univ. J. Sci. 40(1) : 122-147, 2019